Prevalence and Associated Factors of Anemia among Breast Cancer Patients Undergoing Chemotherapy: A Prospective Study - Fares M.S Muthanna (Advances in Pharmacological and Pharmaceutical Sciences, 2022)
Purpose. The purpose of this study was to ascertain the prevalence and factors associated with anemia (hemoglobin [Hb] 12 g/dL) in breast cancer patients undergoing chemotherapy. Materials and Methods. We conducted a prospective longitudinal study to collect demographic and clinical data on adult breast cancer patients with or without anemia who were admitted to HKL, UMMC, and NCI. The incidence of anemia was determined by detecting whether or not anemia developed during the course of chemotherapy. Mild, moderate, or severe anemia was defined. A chi-squared and logistic regression model were used to assess the effect of demographic and clinical factors on the incidence of anemia and multiple logistic regression analysis was used to evaluate the associations of potential risk factors with the presence of CRA. Results. The study enrolled a total of 292 breast cancer patients. Anemia occurred at a rate of 41.1% (n = 120). Our findings indicated that clinical factors such as the number of chemotherapy regimens, dose reduction, and type of chemotherapy, for example, docetaxel, as well as demographic covariates such as age and BMI, all contribute to the incidence of anemia in cancer patients. Conclusions. According to this study, the prevalence of anemia in breast cancer patients is high. Patients' age, BMI, number of chemotherapy regimens, and docetaxel were risk factors; thus, protocols are needed to identify subgroups of breast cancer likely to benefit from novel management strategies.